When Is Digital Censorship Permissible? A Conversation Norms Account - Kim, Tami (Journal of Consumer Research, 2025)
Abstract How do people decide what should—and should not—be censored? Seven studies investigate the psychology of digital censorship regarding user-generated content. Study 1 is inductive, identifying three dimensions—content, intent, and outcomes—along which consumers believe censorship decisions regarding user-generated content should be made. Despite the prevailing practice of content-based digital-censorship decisions—that is, censorship based on whether the focal content includes negative, concrete attributes such as obscene language and violence—people’s acceptance of censorship decisions is determined, in part, by the degree to which the creator’s intent is considered (an “intent-sensitivity hypothesis”; studies 2A–D) even when failing to censor would engender negative consequences. The current research contends that this effect stems from people’s belief that when online platforms make censorship decisions regarding user-generated content, they should abide by conversation norms. Thus, people demonstrate less intent sensitivity in contexts in which doing so is not as conversationally normative—for instance, when platforms are used for professional, rather than social, purposes (study 3). Furthermore, people do not expect the platform to exhibit intent sensitivity in less conversationally intimate contexts (study 4).